Environmental enrichment enhances cognitive flexibility in C57BL/6 mice on a touchscreen reversal learning task. (1st May 2017) - Zeleznikow-Johnston, Ariel; Burrows, Emma L.; Renoir, Thibault; Hannan, Anthony J.
Abstract: Environmental enrichment (EE) is any positive modification of the 'standard housing' (SH) conditions in which laboratory animals are typically held, usually involving increased opportunity for cognitive stimulation and physical activity. EE has been reported to enhance baseline performance of wild-type animals on traditional cognitive behavioural tasks. Recently, touchscreen operant testing chambers have emerged as a way of performing rodent cognitive assays, providing greater reproducibility, translatability and automatability. Cognitive tests in touchscreen chambers are performed over numerous trials and thus experimenters have the power to detect subtle enhancements in performance. We used touchscreens to analyse the effects of EE on reversal learning, visual discrimination and hippocampal-dependent spatial pattern separation and working memory. We hypothesized that EE would enhance the performance of mice on cognitive touchscreen tasks. Our hypothesis was partially supported in that EE induced enhancements in cognitive flexibility as observed in visual discrimination and reversal learning improvements. However, no other significant effects of EE on cognitive performance were observed. EE decreased the activity level of mice in the touchscreen chambers, which may influence the enrichment level of the animals. Although we did not see enhancements on all hypothesized parameters, our testing paradigm is capable of detecting EE-induced improved cognitive flexibility in mice, which has implications for both understanding the mechanisms of EE and improving screening of putative cognitive-enhancing therapeutics. Highlights: Environmental enrichment of mice enhances specific aspects of cognitive performance. Environmentally enriched mice showed enhanced visual discrimination and reversal learning. Cognitive abilities were assessed using automated and translatable touchscreen tests. Touchscreen behavioural batteries may be useful for preclinical testing of cognitive enhancers.